Cosmopolitan India - Rosa Maria Perez (Ateliers d'Anthropologie)
This paper debates the modern conceptualization of cosmopolitanism in the social sciences, grounded on the Indian diaspora in the world. Its main focus is the growing Bollywood cinema in Hindi and the role that it plays in the international consumption of the Indian culture.